Environmental, Energetic, and Economic Comparisons of Organic and Conventional Farming Systems - Pimentel, D.; Hepperly, P.; Hanson, J.; Douds, D.; Seidel, R.
Various organic technologies have been utilized for about 6000 years to make agriculture sustainable while conserving soil, water, energy, and biological resources. Among the benefits of organic technologies are higher soil organic matter and nitrogen, lower fossil energy inputs, yields similar to those of conventional systems, and conservation of soil moisture and water resources (espeeially advantageous under drought conditions). Conventional agriculture can he made more sustainable and ecologically sound hy adopling some traditional organic farming technologies.
Keywords: ORGANIC; AGRICULTURE; CONVENTIONAL